Comparative transcriptome analysis reveals the potential mechanism of GA3-induced dormancy release in Suaeda glauca black seeds - Wang, Hongfei; Xu, Tianjiao; Li, Yongjia; Gao, Rui; Tao, Xuelin; Song, Jieqiong; Li, Changping; Li, Qiuli (Frontiers in Plant Science, 2024)
Suaeda glauca Bunge produces dimorphic seeds on the same plant, with brown seeds displaying non-dormant characteristics and black seeds exhibiting intermediate physiological dormancy traits. Previous studies have shown that black seeds have a very low germination rate under natural conditions, but exogenous GA3 effectively enhanced the germination rate of black seeds. However, the physiological and molecular mechanisms underlying the effects of GA3 on S. glauca black seeds are still unclear. In this study, transcriptomic profiles of seeds at different germination stages with and without GA3 treatment were analyzed and compared, and the TTF, H2O2, O2–, starch, and soluble sugar contents of the corresponding seed samples were determined. The results indicated that exogenous GA3 treatment significantly increased seed vigor, H2O2, and O2– contents but decreased starch and soluble sugar contents of S. glauca black seeds during seed dormancy release. RNA-seq results showed that a total of 1136 DEGs were identified in three comparison groups and were involved mainly in plant hormone signal transduction, diterpenoid biosynthesis, flavonoid biosynthesis, phenylpropanoid biosynthesis, and carbohydrate metabolism pathway. Among them, the DEGs related to diterpenoid biosynthesis (SgGA3ox1, SgKAO and SgGA2ox8) and ABA signal transduction (SgPP2Cs) could play important roles during seed dormancy release. Most genes involved in phenylpropanoid biosynthesis were activated under GA3 treatment conditions, especially many SgPER genes encoding peroxidase. In addition, exogenous GA3 treatment also significantly enhanced the expression of genes involved in flavonoid synthesis, which might be beneficial to seed dormancy release. In accordance with the decline in starch and soluble sugar contents, 15 genes involved in carbohydrate metabolism were significantly up-regulated during GA3-induced dormancy release, such as SgBAM, SgHXK2, and SgAGLU, etc. In a word, exogenous GA3 effectively increased the germination rate and seed vigor of S. glauca black seeds by mediating the metabolic process or signal transduction of plant hormones, phenylpropanoid and flavonoid biosynthesis, and carbohydrate metabolism processes. Our results provide novel insights into the transcriptional regulation mechanism of exogenous GA3 on the dormancy release of S. glauca black seeds. The candidate genes identified in this study may be further studied and used to enrich our knowledge of seed dormancy and germination.